Learning Project Based with the Help of an Android Smartphone on Trigonometry Comparison Material - Istadi, Istadi; Hidayati, Herlina; Rakhmawati, Astri; Muttaqien, Anwar; Kursius, Catherine M. (JUPE : Jurnal Pendidikan Mandala, 2024)
The aim of this research is to describe the use of project-based learning with the help of Android smartphones in trigonometric ratio material in grade X SMAN 1 Kota Besi. This research method is descriptive qualitative. The subjects of this study were tenth grade students SMAN 1 Kota Besi. Based on the results of reflections and interviews, it shows that the use of android aplication in project-based learning, namely (1) makes learning easier for students to understand and learning is more interactive because students experience it for themselves, (2) learning becomes more interesting because they use their gadgets for learning and practicum, and (3) students are more creative because they have to make reports and make presentations in front of the class. Thus the use of android aplication can support project-based learning on trigonometric ratio  material at SMAN 1 Kota Besi both inside and outside the classroom and outside of school.